User centered design principle: safety mobile application / Siti Nurasyikin Mohamad Tamin - Mohamad Tamin, Siti Nurasyikin (2015)
The Lack of awareness of personal safety is a reason why some of people take easier of self-defense. Personal Safety is a freedom from physical harm and threat, aggression, assault causing bodily harm and sexual harassment. While nowadays, the numbers of users having mobile phone is a must and rapidly increased. Hence, it can be used efficiently for personal safety security protection purpose. This study present prototype for user interface safety mobile application. The purpose of this study is to design user interface consideration of User-Centered Design Principle. The design user interface also comply common safety feature by comparing existing safety mobile application features. The research aim is to propose appropriate user interface design for safety mobile application. A prototype of the user interface design were made based on the design requirement obtain through review articles, journals, websites and interviews and also based on the sketches made in early development of the design. The prototype was then improvised in order to provide effective and efficiency design user interface for safety mobile application.